2011
DOI: 10.1007/s11243-011-9564-1
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted aqueous Suzuki coupling reactions catalyzed by ionic palladium(II) complexes

Abstract: Suzuki coupling is one of the most powerful methods for the synthesis of biaryls. We have prepared and characterized a series of unsymmetrical sulfonated watersoluble Pd(II)-pyridyl imine complexes and investigated them as catalysts for the Suzuki cross-coupling reaction in water under microwave irradiation. The compounds proved to be effective catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…As such conversions are reported only for complexes with chloride and not azide as coordinated anion, so the chloro derivatives are chosen. It is found that the catalytic activity of 3 is comparable to IV , Va and Vb in the coupling involving aryl bromides though these complexes are less bulky as compared to 3 , and moreover Va and Vb are water soluble ionic complexes ,. Further, complex IV has not been explored coupling reactions involving chloro substrates whereas Va and Vb show poorer activity than 3 for the same couplings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such conversions are reported only for complexes with chloride and not azide as coordinated anion, so the chloro derivatives are chosen. It is found that the catalytic activity of 3 is comparable to IV , Va and Vb in the coupling involving aryl bromides though these complexes are less bulky as compared to 3 , and moreover Va and Vb are water soluble ionic complexes ,. Further, complex IV has not been explored coupling reactions involving chloro substrates whereas Va and Vb show poorer activity than 3 for the same couplings.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the catalytic activity of 3 is comparable to IV, Va and Vb in the coupling involving aryl bromides though these complexes are less bulky as compared to 3, and moreover Va and Vb are water soluble ionic complexes. [40,41] Further, complex IV has not been explored coupling reactions involving chloro substrates whereas Va and Vb show poorer activity than 3 for the same couplings. On the other hand, 3 is found to be a better catalyst in the coupling involving 4-methoxy bromobenzene and phenyl boronic acid than complex VI, which requires higher catalytic loading for the same conversion though it is also less bulky than 3.…”
Section: Catalytic Studiesmentioning
confidence: 99%
“…The crude material was flash chromatographed on a silica gel column. All of the compounds have been characterized by comparing 1 H-NMR with the values found in the literature [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pyridyl-imine and diimine type ligands are very helpful for designing homogeneous catalysts due to their easily switchable properties, but they suffer from rapid decomposition in water. In this context, Hanhan and Senemoglu [73] have prepared a series of unsymmetrical, ionic sulfonated pyridyl imine ligands and their Pd(II) complexes which are suitable for MW-assisted SMC in water (PyIPd) (Scheme 40). These ionic Pd(II) complexes proved to be effective when used as 0.1 mol % catalysts in water for SMC reactions in the presence of K 2 CO 3 (2 mmol) and terabutylammonium bromide (TBAB) (0.5 mmol), used as the phase transfer reagents.…”
Section: Scheme 35 Novel Bis-benzimidazole Salts Bearing Furfuryl Anmentioning
confidence: 99%